2020
DOI: 10.3390/plants9030364
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Chilli Pepper Genotypes as a Source of Capsaicinoids and Antioxidants under Conditions of Simulated Drought Stress

Abstract: In many regions of the world, the production of vegetable crops is limited by a deepening water crisis. Drought stress affects productivity and the chemical composition of crops. The variability of drought tolerance between species and cultivars of economically important crops, such as pepper (Capsicum species), requires specific investigations to understand the physiological and biochemical responses to the aftermath of drought. The fruits and leaves of four chilli pepper cultivars were investigated to elucid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 43 publications
2
28
0
Order By: Relevance
“…As an appraisal of the potential roles attributed to ascorbate in pepper fruits, it was proposed that in the sweet varieties, ascorbate functions as a redox buffer to balance the great metabolic changes which undergo during ripening [5,7]. Regarding the hot varieties (Padrón and Alegría), the pattern observed in this work where ascorbate levels increased in those fruits was also reported earlier for diverse hot pepper varieties [14,18,50,91]. Perhaps, the redox stabilizing role of ascorbate indicated above for sweet pepper could be also applicable to hot varieties to assure the capsaicinoids level.…”
Section: The Higher Capsaicinoids Level the Higher Ascorbate And Glutsupporting
confidence: 79%
See 3 more Smart Citations
“…As an appraisal of the potential roles attributed to ascorbate in pepper fruits, it was proposed that in the sweet varieties, ascorbate functions as a redox buffer to balance the great metabolic changes which undergo during ripening [5,7]. Regarding the hot varieties (Padrón and Alegría), the pattern observed in this work where ascorbate levels increased in those fruits was also reported earlier for diverse hot pepper varieties [14,18,50,91]. Perhaps, the redox stabilizing role of ascorbate indicated above for sweet pepper could be also applicable to hot varieties to assure the capsaicinoids level.…”
Section: The Higher Capsaicinoids Level the Higher Ascorbate And Glutsupporting
confidence: 79%
“…Excepting Alegría which has been scarcely used for research purposes, reports on the other three varieties can be found in the literature. Thus, Melchor variety has been used to decipher the mechanisms involved in fruit ripening [18,39,66,67] where some of their antioxidant system have been reported to be involved [68]. Variety Piquillo was used as model to address the effects triggered by infection with Verticillum [69][70][71][72] and how to protect pepper plants against it through diverse practices [73,74], as well as to investigate the effect of sanitized sewage sludge on the growth, yield, fruit quality, soil microbial community and the physiology of pepper plants [75,76].…”
Section: The Experimental Design Provided a Gradual Capsaicin Concentmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the pungent level, pepper fruits are ranked on the so-called Scoville scale which assigns a score to each fruit variety. In this scale, the highest value for the most pungent pepper fruit variety is around 3 × 10 6 , pure capsaicin being 16 × 10 6 [14][15][16][17][18]. Capsaicin is an alkaloid with a phenyl-propanoid nature which has given rise to a family of capsaicinoids composed of at least 22 primary compounds.…”
Section: Introductionmentioning
confidence: 99%